Answer: g(x) = (x - 3)² - 3
Explanation:
f(x) = x²
= (x - 0)² + 0
This is comparable to the equation f(x) = (x - h)² + k where h represents the shift to the right and k represents the shift up.
So, 3 to the right means h = 3. 3 down means k = -3
g(x) = [x - (3)]² + (-3)
= (x - 3)² - 3
******************************************************************************************
Answer:
![\bold{-(4x+101)/(8)}](https://img.qammunity.org/2020/formulas/mathematics/high-school/ceplts65aeeg215n0j38cqa7rbu2leswae.png)
Explanation:
![2\bigg((x)/(2)-5\bigg)-(3)/(2)\bigg(x+(7)/(4)\bigg)](https://img.qammunity.org/2020/formulas/mathematics/high-school/lpfl8r2ab91ymlt36kc0xhjaiihlexnuqg.png)
![=2\bigg((x)/(2)\bigg)-2(5) - (3)/(2)(x)-(3)/(2)\bigg((7)/(4)\bigg)](https://img.qammunity.org/2020/formulas/mathematics/high-school/ogoh0yre632u89etonssvnou0ucdrup804.png)
![=(2)/(2)x - 10 - (3)/(2)x-(21)/(8)](https://img.qammunity.org/2020/formulas/mathematics/high-school/7w10sni7m9leosaq02e9dw1xd67l8qs3at.png)
![=(2)/(2)x - (80)/(8) - (3)/(2)x-(21)/(8)](https://img.qammunity.org/2020/formulas/mathematics/high-school/3j1goh1be2yp17fdlgbe0ujuo9x7tn962n.png)
![=(2)/(2)x - (3)/(2)x-(21)/(8)- (80)/(8)](https://img.qammunity.org/2020/formulas/mathematics/high-school/nbnd789j04ofb1h5ryzw7o8zr3xv6y11hh.png)
![=(-1)/(2)x -(101)/(8)](https://img.qammunity.org/2020/formulas/mathematics/high-school/vjepwdqy1nodxni4mp2hx2lall2hyhw8by.png)
![=(-4)/(8)x -(101)/(8)](https://img.qammunity.org/2020/formulas/mathematics/high-school/a9gzlorr7xeyy8423r0mf89co2fhtlarrv.png)
![=(-4x-101)/(8)](https://img.qammunity.org/2020/formulas/mathematics/high-school/2v3zkj0e6g6lo1pppzbiajo5szslmi4b8i.png)
![=-(4x+101)/(8)](https://img.qammunity.org/2020/formulas/mathematics/high-school/j34f9j13kg9zk23ce039id1dw4mwvwgggf.png)